2021
DOI: 10.1016/j.jinf.2021.05.025
|View full text |Cite
|
Sign up to set email alerts
|

Remdesivir treatment and transient bradycardia in patients with coronavirus diseases 2019 (COVID-19)

Abstract: Are antigenic tests useful for detecting SARS-CoV-2 infections in patients accessing to emergency departments? Results from a North-West Italy hospital Dear Editor, In the article "Clinical application of a rapid antigen test for the detection of SARS-CoV-2 infection in symptomatic and asymptomatic patients evaluated in the emergency department: A preliminary report.", 1 Turcato et al. presented a study on the use of rapid antigenic tests (Ag-RDTs) instead of the usual real time reverse transcription polymeras… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
26
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(33 citation statements)
references
References 10 publications
4
26
3
Order By: Relevance
“…Our results demonstrate that bradycardia occurring during remdesivir use might reflect more favourable disease course and has a substantial potential for improving prognostication of patients with COVID-19. Frequency of bradycardia in our cohort (16.8%) was lower than previously reported in smaller patient cohorts (19%-47%) [2][3][4] which could be attributed to differences in baseline age, sex and comorbidity profile of patients. Underlying mechanisms behind bradycardia temporally associated with the administration of remdesivir remain elusive at the moment.…”
contrasting
confidence: 91%
See 2 more Smart Citations
“…Our results demonstrate that bradycardia occurring during remdesivir use might reflect more favourable disease course and has a substantial potential for improving prognostication of patients with COVID-19. Frequency of bradycardia in our cohort (16.8%) was lower than previously reported in smaller patient cohorts (19%-47%) [2][3][4] which could be attributed to differences in baseline age, sex and comorbidity profile of patients. Underlying mechanisms behind bradycardia temporally associated with the administration of remdesivir remain elusive at the moment.…”
contrasting
confidence: 91%
“…Remdesivir is the only antiviral drug currently approved for the treatment of severe COVID-19. It was recently observed that use of remdesivir might be associated with higher frequency of transitory bradycardia, [1][2][3][4] a phenomenon that was reported in 19%-47% of remdesivir-treated patients without clear clinical significance. Since a number of other potentially detrimental cardiovascular adverse events were reported with remdesivir use, 5 understanding clinical consequences of these phenomena is of outmost importance in everyday clinical practice.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, the Indian Council of Medical Research (ICMR) suggested that clinicians and medical centers should consider clinical manifestations of mucormycosis such as sinus pain, nasal congestion on one side of the face, unilateral headache, swelling or numbness of the face, toothache, and floating of the teeth. 9 …”
Section: Discussionmentioning
confidence: 99%
“…Though the incidence of mucormycosis secondary to tooth extraction and floating is extremely low, when it occurs, it may cause significant morbidity and mortality. Recently, the Indian Council of Medical Research (ICMR) suggested that clinicians and medical centers should consider clinical manifestations of mucormycosis such as sinus pain, nasal congestion on one side of the face, unilateral headache, swelling or numbness of the face, toothache, and floating of the teeth 9 …”
Section: Discussionmentioning
confidence: 99%